The Field-in-field technique in esophageal cancer radiotherapy - Tanaka, Hidekazu; Yamaguchi, Takahiro; Hachiya, Kae; Kitahara, Masashi; Matsuyama, Katsuya; Okada, Sunaho; Matsuo, Masayuki (European Journal of Oncology and Environmental Health, 2017)
Background and aim of the work: Radiotherapy plays an important role in the treatment of esophageal cancer at most stages. Some patients undergo T-shaped irradiation that includes the subclavicular region. In this procedure, the cervical region receives a higher dose of radiation than the lower thoracic region because of differences in thickness. We asked whether the field-in-field (FIF) technique would reduce the size of the hot region in T-shaped irradiation. Methods: Our study consisted of 16 patients with esophageal cancer; the prescribed dose was 40 Gy in 20 fractions. The conventional radiotherapy plan included 4 fields: anterior-posterior/posterior-anterior (AP/PA) parallel-opposed fields and right-anterior oblique and left-posterior oblique fields. The FIF plan included an additional subfield, which was generated by copying the PA field. The multileaf collimators of the subfield were manipulated to shield the areas of the planning target volume (PTV) receiving doses ≥107% of the prescribed dose on the beam’s eye view. After dose calculation, weight was shifted from the original PA field to the subfield until the hot spot disappeared. Results: The volumes of the PTV receiving 107% of the prescribed dose, the maximum doses (Dmax) to the PTV and spinal cord, and the homogeneity index of the PTV were significantly smaller in the FIF plan than in the conventional plan. Conclusions: These findings show that the FIF technique improves the dose homogeneity of the PTV and reduces the maximum dose to the spinal cord in thoracic esophageal cancer.